Diseño de un sistema de evaluación del desempeño 360 grados para mejorar las competencias del personal de la empresa “Aníbal car reparación, pintura y mantenimiento de carrocerías” en la provincia del Tungurahua - Manobanda Paucar, Jonathan Mauricio (2022)
The Evaluation 360-degree performance in the workplace is valuable. The present degree work focuses on developing an evaluation tool for the staff of the company Aníbal Car is of descriptive research type the method used is field research where a work was carried out with a sample of the population of 19 people in total (17 men, 2 women). In the first instance, an awareness survey was conducted about the benefits. Subsequently, the performance evaluation of the cardinal and specific competencies was applied, through the analysis of the results we found that the administrative department is on an outstanding scale with an average of 4.05 given that it meets the requirements that the company needs, the Production department is on a good scale with an average of 3.16 in their respective evaluations. The results of the specific competencies analyze that the Head of Human Talent is on an outstanding scale with an average of 4 given that he overshoots in his area of work while the painter is on a Very good scale with an average of 3.35. In the minimum scale is the Maintenance Manager with an average of 3.25 and the electricity assistant with an average of 2.81 found weaknesses and shortcomings in their abilities, analyzed the results the Human Talent department plans an action plan with different activities such as training focused on improving work performance.